Identifying the critical micropores characteristics for the degradation of mechanical properties in automotive wheels - Yisheng Miao; Zhongyao Li; Xuelong Wu; Shuwei Feng; Shihao Wang; Decai Kong; Qinghuai Hou; Xiaoying Ma; Haibo Qiao; Xiang Li; Wenbo Wang; Yuling Lang; et al. (Journal of Materials Research and Technology)
Automotive wheels are critical components for vehicles' safety and durability because their fatigue failure under cyclic loads is unusually catastrophic. Fatigue cracks typically initiate from such defects as gas and shrinkage pores formed during solidification in low-pressure die casting process of wheels. However, it is still largely unknown which micropore characteristic determines the degradation of mechanical properties in aluminum automotive wheels. In this study, X-ray computed tomography (XCT), finite element analysis (FEA), and digital image correlation (DIC) were employed to investigate the effects of micropore size, morphology and distribution on the mechanical properties at different wheel locations. It has been discovered that, using multiple machine learning methods, the ratio of the projected area of micropores to their shortest distance from the free surface (PA/SD) exhibits the strongest correlation with the stress concentration factor (Kt) around the micropores, achieving a correlation coefficient of 0.90 and demonstrating a linear relationship. DIC and three-dimensional fracture analysis confirmed that regions with high PA/SD values are the primary cause of strain concentration, leading to crack initiation. Therefore, methods of effectively eliminating large micropores near the edges can significantly enhance the mechanical properties of automotive wheels.